The Effect of The Minimum Age Limit for Marriage After The Enactment of Law Number 16 of 2019 Concerning Amendments to Law Number 1 of 1974 Concerning Marriage on The Determination of Marriage Dispensation at The Lumajang Religious Court - Muhammad Faiqul Hammam Novriansyah (Faculty of Law, Universitas Airlangga, 2023)
AbstractMarriage is a legal act. As a legal act, the legal subject who conducts an event must meet the requirements. One of the requirements for humans as legal subjects to be able to be declared capable of carrying out legal actions is to be mature, while the determination of the age limit of children contained in the construction of legislation in Indonesia varies. Likewise, the age limit relates to the rights given to someone when he is considered capable of acting in law, in this case, in carrying out marriage. Marriage is not only an inner bond but a bond between the two. Inner birth ties in marriage mean that between the husband and wife in question, there must be a genuine intention to create a happy and eternal family. Generally, every person who wants a family is sure that his household will want to live harmoniously. Keywords: Marriage; Immature People; Quality Offspring.